Micro–nano NiO-MnCo2O4 heterostructure with optimal interfacial electronic environment for high performance and enhanced lithium storage kinetics. Issue 31 (30th July 2020) - Dang, Wei; Tang, Xincun; Wang, Wei; Yang, Yun; Li, Xing; Huang, Liuchun; Zhang, Yi
Abstract : A uniform NiO-MnCo2 O4 heterostructure with optimal interfacial electronic environment resulted in excellent long-term performances and enhanced reaction kinetics for LIBs. Abstract : This manuscript provides an in situ synthesis method for the self-assembly of a heterostructured NiO-MnCo2 O4 micro–nano composite with a poriferous shell. The special shell structure effectively alleviated the volume variation and subsequently enhanced the diffusivity of ions in the cycling process for cyclic stability. The inner spaces among the stacked nanoparticles are conducive to electrolyte infiltration and the transfer of ion/electrons with low concentration polarization. Consequently, the optimized NiO-MnCo2 O4 exhibited excellent cycle stability (718.8 mA h g −1 after 1000 cycles at 2 A g −1 ) and highly recoverable rate performance. On gaining insight into the heterointerface structure, it was indicated that the optimal interfacial electronic environment in the presence of the nickel content plays a key role in creating lattice defects and active sites to increase the ion diffusion rate, electron conductivity and unlock extra pseudocapacitance for ion storage. The excellent capabilities from the optimal heterointerface environment will promote the development of high-energy applications of LIBs.